Cyber crime and the victimization of women laws, rights and regulations - Halder, Debarati, 1975- (Information Science Reference, 2012)
"This book investigates cyber crime, exploring gendered dimensions of cyber crimes like adult bullying, cyber stalking, hacking, defamation, morphed pornographic images, and electronic blackmailing"--Provided by publisher.